2018
DOI: 10.1088/1361-6587/aae038
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fast electrons on pellet injection in the stellarator TJ-II

Abstract: Efficient plasma core fuelling is a critical issue for achieving steady-state scenarios in magnetically confined fusion devices. The current preferred method to achieve this goal is cryogenic pellet injection (PI). PI's are now installed in most medium-and large-sized fusion devices. In this paper, recent results from PI experiments in the stellarator TJ-II are reported. Of particular interest is the influence of fast electrons. Whilst edge populations of such electrons do not affect PI in the TJ-II, fast elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…However, when a fast-electron population exists in the core when an injection is made (i.e. inside ρ = 0.4), then pellet penetration is truncated and fuelling increase by up to 50% [56]. Simulations of post-injection electron density profiles made with the TJ-II HPI2 code are in good agreement with Thomson scattering density profiles for the former case.…”
Section: Plasma Core Fuelling Pellet Physics and Modellingmentioning
confidence: 53%
See 1 more Smart Citation
“…However, when a fast-electron population exists in the core when an injection is made (i.e. inside ρ = 0.4), then pellet penetration is truncated and fuelling increase by up to 50% [56]. Simulations of post-injection electron density profiles made with the TJ-II HPI2 code are in good agreement with Thomson scattering density profiles for the former case.…”
Section: Plasma Core Fuelling Pellet Physics and Modellingmentioning
confidence: 53%
“…With the expansion of the TJ-II pellet database it has been observed that pellet fuelling efficiency can benefit from the presence of a population of fast electrons in its plasma core [56]. In fact, for ECRH plasmas, it has been determined that when no fast electrons are detected (by hard x-ray emissions or by excess pellet ablation), this efficiency is typically well below 30%.…”
Section: Plasma Core Fuelling Pellet Physics and Modellingmentioning
confidence: 99%
“…Thus, the effect of fast ions on pellet ablation is regarded as insignificant. On the other hand, over-ablation by fast electrons has been reported in the TJ-II [35], where the plasma and heating parameters are similar to those in the Heliotron J. In future studies, we should measure the fast electron energy distribution using a pulse height analyzer and utilize a new ablation code that incorporates the effect of fast electrons on pellet ablation.…”
Section: Discussion: Different Penetration Depths In Nbi+ech and Nb...mentioning
confidence: 97%
“…Indeed, tracer injections with polystyrene (-C 8 H 8 -) based TESPELs have confirmed an inverse mass dependence of the acceleration [16]. Additional experiments have also revealed that enhanced pellet ablation in the plasma core due to fast-electron impacts can lead to higher fuelling efficiencies as the outward drift acceleration is disrupted in the initial drift phase [17]. In particular, it is found that if a pellet is subject to excess ablation due to core fast electron impacts, the resultant pellet efficiency (deposited particles/delivered particles) increases by up to 50% with respect to injections into similar, fast-electron free, plasmas.…”
Section: Plasma Fuelling and Impuritiesmentioning
confidence: 94%